"Indian Country" on Washington's Mall - The National Museum of the American Indian: A Review Essay - Berlo, Janet Catherine; Jonaitis, Aldona (University of California Press Journals. Used with permission., 2007)
Published in 2005 in _Museum Anthropology_, a University of California Press journal. Berlo and Jonaitis review the museum design and the opening exhibits of National Museum of the American Indian (NMAI). They also address some of the reviews the NMAI recieved in the national press.